1981
DOI: 10.1902/jop.1981.52.12.719
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Root Resections: A Ten‐Year Study

Abstract: A study was undertaken to evaluate the long term results of root resections. Records of 100 patients who had undergone root resections 10 years prior to the study were reviewed. Although the immediate postoperative results were gratifying, they were not always lasting. Eighty-four per cent of the failures occurred after 5 years. Most failures were in the mandibular arch and derived from reasons other than inflammatory periodontal disease. Suggestions are made as to how to improve the prognosis of resected teet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
93
2
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(106 citation statements)
references
References 4 publications
5
93
2
5
Order By: Relevance
“…Sin embargo, a pesar de que algunos autores han informado de buenos resultados (38,39), cuando se evalúa el desempeño en el largo plazo se encuentran tasas de fracaso que van desde el 32% (40) hasta el 38% (41). A pesar de que la causa principal de fracaso fuese periodontal, es incierto si puede esperarse una alta incidencia de fracturas radiculares como lo sugieren algunos estudios (41,42).…”
Section: Desafíos Periodontalesunclassified
“…Sin embargo, a pesar de que algunos autores han informado de buenos resultados (38,39), cuando se evalúa el desempeño en el largo plazo se encuentran tasas de fracaso que van desde el 32% (40) hasta el 38% (41). A pesar de que la causa principal de fracaso fuese periodontal, es incierto si puede esperarse una alta incidencia de fracturas radiculares como lo sugieren algunos estudios (41,42).…”
Section: Desafíos Periodontalesunclassified
“…However, predictable regeneration cannot be achieved in advanced furcation invasions due to the complexity of furcation morphology [4]. Multiple modalities have been utilized over the years ranging from non-surgical therapy [3], surgical therapy utilizing regenerative methods using grafts and membranes [5,6,7] , root resection [8 ], tunnel procedure [9] with unpredictable success. The patients are most often offered options which are unpredictable, more invasive and expensive.…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators 4,5 reported that rootresected molars had more than 90% survival rate, whereas other investigators [6][7][8][9] reported that ~30% of resected molars failed over a 10-year period. Some investigators compared the prognosis of root-resection therapy to that of implant therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The most important factors for the prognosis of root-resection therapy have been suggested. [4][5][6][7][8][9]12,13 The following should be considered when deciding which root should be retained: the amount of supporting tissue around the roots, the root and root canal anatomy in relation to the endodontic treatment, the periapical condition, and the mobility of each separated root. 13 Molars with minimal supporting bone or deep osseous craters in the furcation area are poor candidates for root-resection therapy as a result of the recurrent periodontal breakdown of resected molars.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation